1976
DOI: 10.1002/pssa.2210370112
|View full text |Cite
|
Sign up to set email alerts
|

The potential energy curve of the proton and the dissociation energy of the OH− ion in Mg(OH)2

Abstract: The overtone and combination bands, Eon, of the infrared‐active (vu) and Raman active (vg) OH stretching vibrations of Mg(OH)2 are measured (values for Mg(OD)2 in brackets). Fundamentals E01 vu at 3697 (2720) cm−1 and vg at 3655 cm−1; first overtone E02: vu + vg at 7154 (5305) cm−1; second overtone E03; 3vu at 10480 (7830) cm−1; third overtone E04: 3vu + vg at 13640 (10250) cm−1; fourth overtone E05: 5vu or 3vu + 2vg at 16610 cm−1; fifth overtone E06 at 19320 cm−1. The isotope shift factor (theoretical 1.37) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

1977
1977
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 9 publications
2
11
1
Order By: Relevance
“…The effect of the formation of H bonding does not seem to affect the compression behavior nor the Mg-O sublattice, because present data does not show any discontinuity in either unit-cell change or the atomic displacement at about 5 GPa. Brought to you by | New York University Bobst Library Technical Services Authenticated Download Date | 9/29/15 9:59 AM Martens and Freund (1976) suggested that the shortening of the interlayer O ... O distance enhances proton transfer from donors to acceptors of O atoms. Indeed, Shinoda and Aikawa (1998) explained the pressure dependence of IR absorbency by the increasing proportion of proton transfer between interlayers with pressure.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of the formation of H bonding does not seem to affect the compression behavior nor the Mg-O sublattice, because present data does not show any discontinuity in either unit-cell change or the atomic displacement at about 5 GPa. Brought to you by | New York University Bobst Library Technical Services Authenticated Download Date | 9/29/15 9:59 AM Martens and Freund (1976) suggested that the shortening of the interlayer O ... O distance enhances proton transfer from donors to acceptors of O atoms. Indeed, Shinoda and Aikawa (1998) explained the pressure dependence of IR absorbency by the increasing proportion of proton transfer between interlayers with pressure.…”
Section: Resultsmentioning
confidence: 99%
“…02 through equations (1) and (2) for the IR mode only. Actually the attribution of the frequencies at 7157 (brucite) and 7084 cm À1 (portlandite) to the IR overtone, rather than to a combination of the IR and Raman fundamental frequencies as proposed by Mitra [35] and other authors [36,37], leaves some marginal doubt about the proposed ! e x e values.…”
Section: Comparison With Experimentsmentioning
confidence: 97%
“…Graham (1981) proposed that the transport of hydrogen in epidote and zoisite is preceded by hydrolysis of the Si-O and Al-O bonds, followed by a proton transfer by a slower diffusion of (OH) or H 2 O. OH or H 2 O species are unlikely to diffuse in hydrous minerals, especially at low temperature, because of the donors OH and the acceptors O′ in the neighboring layer), and simultaneously increases the strength of the bonding between H and O atoms in the next layer. The potential barrier between proton sites in adjacent OH − groups is proportional to the O … O′ distance (Martens and Freund 1976). Therefore the proton migration through Equation 11 is enhanced by compression.…”
Section: Pressure Effect On the Proton Diffusivity In Brucitementioning
confidence: 98%
“…The previous studies focused on whether brucite forms pressure-induced hydrogen bonds between hydroxyls on a brucite layer and oxygen atoms on the adjacent layer or not (Sherman 1991;D'Arco et al 1993;Parise et al 1994;Catti et al 1995). The study of Martens and Freund (1976) suggested that the potential barrier for proton transfer between two neighboring hydrogen atoms in brucite would be reduced by compression. The infrared (IR) study of Shinoda and Aikawa (1998) and theoretical calibrations by Mookherjee and Stixrude (2006) have both shown that the proton transfer across the interlayer might be strongly * E-mail: gxzhuan@misasa.okayama-u.ac.jp enhanced under pressure, that is, the pressure has a positive effect on the mobility of proton.…”
Section: Introductionmentioning
confidence: 96%